Autoimmune Hemolytic Anemia (AHA) with hyperglycemia in a 22-year-old woman: a case report - Fran Siska; Saskia Ramadhani; Anik Widijianti (DiscoverSys Inc., 2022)
Background: Autoimmune hemolytic anemia (AIHA) is defined as increased erythrocyte destruction due to anti-erythrocyte autoantibodies with or without complement activation. Diabetes Mellitus (DM) is a chronic metabolic disease characterized by elevated blood glucose levels, which cause serious damage to various organs, including the heart, blood vessels, eyes, kidneys, and nerves. The impact of DM on a patient's survival with AIHA is unknown. Case Presentation: A 22-year-old woman complained of dizziness and fainting before admission. The patient looked pale; on physical examination, we found jaundice on the sclera. This patient was diagnosed with AIHA and DM with increased HbA1c (10.8%) since 2017 but did not take the anti-diabetic drugs regularly. Hematological examination showed anemia, increased reticulocytes, and a positive direct Coombs test. The result of increased fasting glucose, 2 hours OGTT, and HbA1c levels (4.6%) tests were not relevant to hyperglycemia. In this patient, we also found normal C-peptide levels. The decrease in HbA1c levels was thought to be due to hemolytic anemia; therefore, HbA1c was falsely low due to rapid erythrocyte turnover. Conclusion: This patient was diagnosed with DM based on American Diabetes Association criteria with normal C-peptide levels, suggesting Maturity Onset Diabetes of the Young with HbA1c incompatibility with glucose levels may be due to rapid erythrocyte turnover.